High temperature tribological studies of cold sprayed nickel based alloy on low carbon steels. (2020) - Padmini, B.V.; Mathapati, Mahantayya; Niranjan, H.B.; Sampathkumaran, P.; Seetharamu, S.; Ramesh, M.R.; Mohan, N.
Abstract: The boiler steels of grades SAE213 T11 and T22, find extensive applications in heat exchanger tubes, paper and pulp, chemical industries and refineries. Further, these steels are also used in shafts, cylinders, bearings, and in automotive transmission parts and these aspects are less explored. They experience low wear life in specific components, both at room and slightly higher temperature regimes. In order to protect them from these damages, coatings are deployed involving many techniques like HVOF, Plasma spray, Cold spray etc. so that the life of the components get extended. In cold spray coatings, the powders are fed at very high impact velocities of up to 1200 m/s on the substrate and undergo plastic deformation during the impact. There is no oxidation of the powder takes place during the process, as the coating is done at very less temperature and this is one of the lead characteristic of cold spray technique. This particular work mainly focuses on evaluating the tribological behaviour of nickel based super alloy powder on T11 and T22 low alloy steels by cold spray method, using pin on disc machine both at room temperature as well as at 200, 300 and 400 °C. The associated tests such as hardness, porosity, and microstructure have been undertaken to support the wear data. The wear damage assessment has been carried out using scanning electron microscope to arrive at the mechanism and also to give credence to the wear data.